Air Gun Pellet–Induced Penetrating Abdominal Injury Presenting with Peritonitis and Jejunal Perforation Managed by Emergency Laparotomy: A Case Report - Habib Husein Jasman; Suindra Suindra (Jurnal Ners, 2026)
Air gun projectiles are capable of generating sufficient kinetic energy to penetrate the abdominal wall and injure intra-abdominal organs. Despite this, such injuries are frequently underestimated in clinical practice, which may delay recognition of significant internal damage. Penetrating abdominal trauma involving hollow viscus structures presents a diagnostic challenge due to variable clinical manifestations. Current management strategies are determined by hemodynamic status and clinical findings, particularly the presence of peritoneal signs, which constitute a direct indication for operative intervention. A 39-year-old male presented with progressive abdominal pain one day after sustaining an air gun injury to the abdomen. Physical examination revealed abdominal distension, diffuse tenderness, and muscular guarding. Laboratory evaluation showed leukocytosis. Plain abdominal radiography demonstrated a radiopaque foreign body localized at the level of the fifth lumbar vertebra. The patient underwent emergency exploratory laparotomy. Intraoperative findings revealed jejunal perforation and a retained projectile, which was successfully extracted. Bowel resection followed by primary end-to-end jejunojejunal anastomosis was performed. The postoperative course was uneventful, and the patient was discharged on postoperative day eight. Penetrating abdominal trauma caused by air gun projectiles may result in hollow viscus injury requiring surgical management. The presence of peritoneal signs constitutes a direct indication for immediate laparotomy, while non-operative management is reserved for selected patients without clinical evidence of peritoneal irritation.